Multilevel tree optical switching network technology in smart substation - Xiaojian ZHANG; Yu ZHENG (Dianxin kexue)
Communication network in smart substation carries monitoring and protection services,with real-time and reliability requirements.Based on the analysis of communication services characteristics in smart substation,a multilevel tree optical switching network architecture was proposed based on optical burst switch mechanism.Then,based on the structure and function of the primary node,slave node and edge node of optical switching network,and GOOSE,SV data flow in process layer network was analyzed.Finally,the communication process of the master node control plane based on the Round-Robin scheduling algorithm was described.